2021
DOI: 10.1038/s41598-021-81180-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and hospitalisation due to diabetic ketoacidosis and hypoglycaemia in individuals with type 1 diabetes

Abstract: We investigated the association between diet and risk of hospitalisation for diabetic ketoacidosis (DKA) or hypoglycaemia in type 1 diabetes. Food records were used to assess dietary intake. Data on DKA and hypoglycaemia hospitalisations, within two years of dietary assessments, were obtained from registries. Analyses were conducted with and without macronutrient substitution. Data were available from 1391 participants, 28 (2.0%) and 55 (4.0%) of whom were hospitalised due to DKA or hypoglycaemia, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our results suggest that increasing fiber intake and exchanging fats and carbohydrates with protein could lead to better glucose control in type 1 diabetes. Our results were in line with another study of diet composition in individuals hospitalized for ketoacidosis, where those with high fiber intake were less likely to be hospitalized for ketoacidosis ( 36 ). Interestingly, persons with a higher median percentage of energy intake, derived from carbohydrates were more likely hospitalized for severe hypoglycemia (45,5% vs. 43,6% in those with hospitalization for severe hypoglycemia vs. those without, respectively).…”
Section: Nutrition - Meeting Diet Recommendations Glycemic Control An...supporting
confidence: 92%
“…Our results suggest that increasing fiber intake and exchanging fats and carbohydrates with protein could lead to better glucose control in type 1 diabetes. Our results were in line with another study of diet composition in individuals hospitalized for ketoacidosis, where those with high fiber intake were less likely to be hospitalized for ketoacidosis ( 36 ). Interestingly, persons with a higher median percentage of energy intake, derived from carbohydrates were more likely hospitalized for severe hypoglycemia (45,5% vs. 43,6% in those with hospitalization for severe hypoglycemia vs. those without, respectively).…”
Section: Nutrition - Meeting Diet Recommendations Glycemic Control An...supporting
confidence: 92%
“…The COI includes measures such as reading and math proficiency, adult educational attainment, and access to healthy food, all of which are particularly important for children living with T1D because they must calculate insulin dosing, manage diabetes technology (eg, insulin pumps), and find healthy food choices. The importance is further supported by previous work showing that the risk of DKA and glycemic excursions are associated with lower parental educational level and unhealthy dietary intake choices . In addition, household food insecurity has been associated with higher hemoglobin A 1c values and hospitalization rates in children with T1D, which is notable because children with lower COI categories have more limited access to healthy food choices compared with those with higher COI categories .…”
Section: Discussionmentioning
confidence: 64%
“…The importance is further supported by previous work showing that the risk of DKA and glycemic excursions are associated with lower parental educational level 10 , 11 , 42 and unhealthy dietary intake choices. 43 , 44 , 45 , 46 In addition, household food insecurity has been associated with higher hemoglobin A 1c values and hospitalization rates in children with T1D, 47 which is notable because children with lower COI categories have more limited access to healthy food choices compared with those with higher COI categories. 13 , 48 , 49 Less frequent use of diabetes technology, particularly continuous glucose monitoring devices, has also been associated with worse health outcomes in children with T1D, including higher rates of DKA 50 and time spent in hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study involving adolescents with T1D suggested that eating disorders have more than triple the risk of DKA [ 16 ]. Another study investigated the association between different diet composition and risk of DKA in T1D [ 17 ]. Due to leptin’s acute insulin-independent effect to reverse DKA [ 18 ], and increased leptin secretion by food intake [ 19 21 ], we hypothesize that leptin may mediate the relationship between the timing of the initiation of dietary intake and DKA correction as an internal mechanism.…”
Section: Discussionmentioning
confidence: 99%